Dampak Keteladanan Guru Sekolah Minggu Dalam Pembentukan Karakter Anak Di Gereja Kristen Indonesia Menining - Vera Ria Christia; Christiani Hutabarat (Journal of Religious and Socio-Cultural, 2021)
The teacher's example in character building is the beginning of making quality Sunday school children. The example of Sunday school teachers is the basis for producing children with good character. It turns out that in creating the formation of children's character, it must be based on various aspects, one of which is seen from the teacher so that children can imitate the attitudes and examples of their own teachers. The main purpose of this paper is to find out how influential the role model of a Sunday school teacher is in shaping the character of children at Gereja Kristen Indonesia Menining. This writing uses the type of Qualitative research that uses direct interview techniques with Sunday school children and Sunday school teachers. From this writing, it can be concluded that 1). The example of Sunday school teachers greatly influences the formation of children's character. 2). In improving the character of children, they can go through the surrounding environment. 3). The example of the Sunday school teacher is the basis for the formation of the child's character, and the Sunday school teacher must also be a good example for Sunday school children. 4). Various tools and facilities that support in creating a comfortable atmosphere are needed in the teaching process Keteladanan guru dalam pembentukan karakter merupakan awal menjadikan anak sekolah minggu yang berkualitas. Keteladanan guru sekolah minggu menjadi dasar agar menghasilkan anak yang berkarakter yang baik. Ternyata dalam menciptakan pembentukan karakter anak harus didasari oleh berbagai aspek salah satunya adalah dilihat dari gurunya sehingga anak dapat menirukan sikap dan keteladanan yang dimiliki oleh gurunya sendiri. Tujuan utama dari penulisan ini adalah agar mengetahui seberapa berpengaruhnya keteladana seorang guru sekolah minggu dalam pembentukan karakter anak Di Gereja Kristen Indonesia Menining. Penulisan ini mengunakan jenis penelitian Kualitatif yang mengunakan Teknik wawancara langsung dengan anak sekolah minggu dan para guru sekolah minggu. Dari penulisan ini maka dapat di simpulkan bahwa 1). Keteladanan guru sekolah minggu sangat mempengaruhi dalam pembentukan karakter anak. 2). Dalam meningkatkan karakter anak dapat melalui lingkungan sekitar. 3). Keteladanan yang dimiliki guru sekolah minggu menjadi dasar pembentukan karakter anak, dan guru sekolah minggu juga harus bisa menjadi contoh yang baik bagi anak sekolah minggu. 4). Berbagai alat dan sarana yang menjadi pendukung dalam menciptakan suasana yang nyaman sangat dibutuhkan dalam proses mengajar